The Advertising-Value-Equivalent (AVE) Method in Quantifying Economic Values of Public Relations Activities: Experience of a Public-Listed Company in Malaysia - Chang Peng Kee,; Musa Abu Hassan, (Kajian Malaysia, 2006)
Why should public relations (PR) not be evaluated for its economic value? Despite the point of its social or intangible values, the argument goes on and on in most management meetings where PR practitioners always face the challenges of justifying their worth – often in monetary terms. In an open dialogue with Grunig during his visit to Malaysia in 2004, this renowned PR guru also expressed the difficulty of quantifying the actual PR worth. It is best to qualify PR values by assessing its priceless relationships with the company’s stakeholders. However, in our routine business life, especially at the middle management level, the above question seems unavoidable. In enhancing excellence for PR and communication management, Ehling (1992) placed the logic underlying the economic values of PR on the relationship between benefits and costs associated with the implementation of a PR programme. The above question and problem serve as the main objective of this article. In exploring the solutions for the quantification of PR values in Malaysia, economic education is taken as a remedy for the absence of knowledge and skills in making intelligent decisions in the marketplace (Baskin et al., 1997; Lattimor et al., 2004). In this research context, the researchers (a combination of a practitioner and an academician respectively) confined the scope to the experience of a selected publiclisted company for its PR campaign implemented in 2004. Quantification was attempted by evaluating the assessment in print media exposures. All earned media coverage for that particular PR campaign was measured for the media type, space, position, and the corresponding advertising rate. Monetary value was assigned to every single piece of PR news in the way disbursements are made to paid media for advertising activities. The explication of this advertisingvalue-equivalent (AVE) method in quantifying economic values for PR news with regard to the selected campaign was made possible with specially designed computer software. The report generated from the said software showed that the cumulative AVE was able to explain the return on expenditure (ROE) in order to carry out the said campaign. The propagation of the above AVE can be one of the many solutions to evaluate the economic worth of PR.